PENINGKATAN PENGUASAAN KOSAKATA BAHASA INGGRIS MELALUI PERMAINAN AKADEMI MEMASAK PADA SISWA KELAS X DI SMK NEGERI 1 PANJI SITUBONDO TAHUN PELAJARAN 2019 – 2020 - hari murdianti (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2022)
This is a classroom action research aiming at finding out to what extent CookingAcademy, a cooking simulation game created by Fugazo, Inc., enriches vocational students’ vocabulary dealing with cooking. I found that the students of Teknologi Pengolahan Hasil Pertanian (TPHP) or Technology of Processing Agriculture Produce class’ main problem in mastering and using English was vocabulary. Thus, I expected that Cooking Academy game might enrich their vocabulary. The participants of the research were 32 tenth graders majoring in TPHP of SMK N 1 Panji in the academic year of 2019/2020. The method of collecting data in this research was mixed-method using qualitative data and supported by quantitative data. The participants were given materials dealing with vocabulary used in cooking activities. According to the analyses, the pre-test mean was 42.30, while the post- test mean was 78.95. Between pre-test and post-test, they were given two quizzes, quiz 1 and 2 with the mean of 84.84 and 86.09 respectively. The students’ participation and attitude during the treatment showed that they appreciated the Cooking Academy game I used in the teaching and learning process. Based on the results, it could be concluded that there was animprovement of the students’ score at 86.6%. So, the Cooking Academy game enriched the vocational students’ vocabulary dealing with cooking